2021
DOI: 10.1186/s13018-021-02690-1
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside positively regulated osteogenic differentiation of pre-osteoblast MC3T3-E1 through PI3K/Akt signaling pathway

Abstract: Background Osteoporosis is a widespread chronic disease characterized by low bone density. There is currently no gold standard treatment for osteoporosis. The aim of this study was to explore the role and mechanism of Astragaloside on osteogenic differentiation of MC3T3-E1 cells. Methods MC3T3-E1 cells were divided into control and different dose of Astragaloside (10, 20, 40, 50, and 60 μg/ml). Then, ALP and ARS staining were performed to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In the process of osteogenic differentiation of BMSCs, the ALP enzyme is active in the early stage . With the passage of time, the activity of ALP decreases, while the calcium nodules gradually come into formation. , Therefore, in the late stage of the BMSC osteogenesis process, the osteogenic activity of BMSCs can be better reflected by detecting the formation of calcium nodules. Moreover, judging the osteogenic ability of BMSCs can also be achieved by detecting osteogenesis-related genes and osteogenesis-related proteins by PCR and WB experiments, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the process of osteogenic differentiation of BMSCs, the ALP enzyme is active in the early stage . With the passage of time, the activity of ALP decreases, while the calcium nodules gradually come into formation. , Therefore, in the late stage of the BMSC osteogenesis process, the osteogenic activity of BMSCs can be better reflected by detecting the formation of calcium nodules. Moreover, judging the osteogenic ability of BMSCs can also be achieved by detecting osteogenesis-related genes and osteogenesis-related proteins by PCR and WB experiments, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, astragaloside is implicated with the osteogenic differentiation of pre-osteoblast MC3T3-E1 in osteoporosis via mediating the PI3K/Akt signaling pathway. 24 Neohesperidin participates in bone mesenchymal stem cells' osteogenic differentiation through adjusting the Wnt/βcatenin signaling pathway in osteoporosis. 25 Arbutin modulates autophagy in osteoblasts to suppress the glucocorticoid-triggered osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have illuminated that there were a variety of herbs involved in the development of osteoporosis. For instance, astragaloside is implicated with the osteogenic differentiation of pre‐osteoblast MC3T3‐E1 in osteoporosis via mediating the PI3K/Akt signaling pathway 24 . Neohesperidin participates in bone mesenchymal stem cells' osteogenic differentiation through adjusting the Wnt/β‐catenin signaling pathway in osteoporosis 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In osteoporosis, the PI3K/Akt signaling cascade is triggered, which performs a fundamental function in the osteoclast’s hyperactivation as well as the differentiation and maturation of osteoblasts ( Han et al, 2021 ). Astragaloside positively regulated osteogenic differentiation of MC3T3-E1 by triggering the PI3K/Akt signaling pathway ( Jing et al, 2021 ). Research has found that dexamethasone inhibits the osteogenic differentiation of osteoblasts in vivo and in vitro via the PI3K/Akt signaling pathway ( Pan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%